2014
DOI: 10.1200/jco.2014.57.3055
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Testing for Selection of Patients With Lung Cancer for Epidermal Growth Factor Receptor and Anaplastic Lymphoma Kinase Tyrosine Kinase Inhibitors: American Society of Clinical Oncology Endorsement of the College of American Pathologists/International Association for the Study of Lung Cancer/Association for Molecular Pathology Guideline

Abstract: Purpose The College of American Pathologists (CAP), the International Association for the Study of Lung Cancer (IASLC), and the Association for Molecular Pathology (AMP) guideline on molecular testing for the selection of patients with lung cancer for epidermal growth factor receptor (EGFR) and anaplastic lymphoma kinase (ALK) tyrosine kinase inhibitors was considered for endorsement. Methods American Society of Clinical Oncology (ASCO) staff reviewed the CAP/IASLC/AMP guideline for developmental rigor; an ASC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
176
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(180 citation statements)
references
References 3 publications
0
176
0
4
Order By: Relevance
“…The IASLC approval process required review and approval by the IASLC Board of Directors. The AMP approval process required content review by an independent subject matter expert panel, led by the Publications & Communications chair, with 4 our opinion remains that each institution should set its own policy regarding testing patients with early-stage disease, balancing the benefit of having results on record from testing a high-quality resection sample for alterations that are likely to become necessary at a time of future progression when a high-quality sample could be hard to obtain against the cost of testing patients for whom a subset will be surgically cured and never need the test result. Accordingly, the testing recommended below applies to patients with advanced-stage (stages IIIB and IV) lung cancer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The IASLC approval process required review and approval by the IASLC Board of Directors. The AMP approval process required content review by an independent subject matter expert panel, led by the Publications & Communications chair, with 4 our opinion remains that each institution should set its own policy regarding testing patients with early-stage disease, balancing the benefit of having results on record from testing a high-quality resection sample for alterations that are likely to become necessary at a time of future progression when a high-quality sample could be hard to obtain against the cost of testing patients for whom a subset will be surgically cured and never need the test result. Accordingly, the testing recommended below applies to patients with advanced-stage (stages IIIB and IV) lung cancer.…”
Section: Resultsmentioning
confidence: 99%
“…In 2013, this working group published an evidence-based guideline 1e3 for standard-of-care clinical practice concerning which lung cancer patients and samples should be tested, which genes should be tested, and how these tests should be designed, validated, and executed. This guideline was subsequently endorsed by the American Society of Clinical Oncology, 4 and has been cited in guidelines developed by numerous professional societies around the world. 5e26 However, the field has continued to advance rapidly, with the emergence of new genetic discoveries, new therapies, and new technologies, such that these same 3 organizations convened a second working group to systematically assess new evidence and to issue an evidence-based revision of the lung cancer molecular pathology practice guideline.…”
mentioning
confidence: 99%
“…Laboratory Improvement Amendments (CLIA) certified laboratory, following CLSI EP7-A2 and published guidelines (30,31). The analytical validation was designed to address precision (repeatability and reproducibility), sensitivity (limit of detection), specificity, and the effect of interfering substances.…”
Section: Analytical and Clinical Validation Of The Test Was Performedmentioning
confidence: 99%
“…However, the current system of biomarker testing practice poses significant challenges: more than half of all responding specialists reported that fewer than 25% of test results are provided in time for firstline treatment decisions. An American Society of Clinical Oncology review panel recently endorsed the guidelines for molecular testing published by the College of American Pathologists, the International Association for the Study of Lung Cancer, and the Association for Molecular Pathology, which recommended testing for EGFR mutations and ALK fusions in all patients with advanced-stage adenocarcinoma to guide patient selection for targeted therapies 15 . That endorsement highlighted the clinical importance of early molecular diagnosis in determining appropriate treatment plans for patients with advanced lung cancer.…”
Section: Discussionmentioning
confidence: 99%